SUG‘ORILADIGAN YERLARDA XO‘RAKI KO‘K NO‘XATNING O‘SUV DAVRI DAVOMIYLIGINI IRSIYLANISH DARAJASINI ANIQLASH. (AGROINNOVATSIYА, 2024)
As a result of the research conducted in this article, the heredity of F1 hybrids obtained by crossing lines of blue peas (P. sativum) and varieties intended for planting on irrigated lands was established, according to the duration of the growing season. appreciated.